STUDI KASUS : Implementasi Asuhan Keperawatan Pada Ny.R (G2P1A0) Dengan Hiperemesis Gravidarum Pada Trimester II Kehamilan - Roosmalinda Rezk Amalia (2022)
Background: Hyperemesis gravidarum is excessive nausea and vomiting usually in the first trimester of pregnancy which can interfere with daily activities and the general condition of the mother worsens and is at risk of abnormality in the fetus. The need to treat nausea and vomiting, and increase nutritional intake. Knowing the factors that cause and how to handle Hyperemesis Gravidarum with nursing care in order to reduce the incidence and risk due to Hyperemesis Gravidarum. There are psychological factors and history in the case study that can cause HEG in Mrs. R in the second trimester. Methods: This study uses the case study method in implementing nursing care for Mrs. R (G2P1A0) in the second trimester of pregnancy at RT 006 RW 015, Kelurahan Pancoran Mas, Pancoran Mas Sub-district, Depok City on June 12, 2021-14 June 2021. Data collection was carried out by interviews, observation and physical examination, as well as documentation. Measurements using a nausea and vomiting questionnaire, namely PUQE-24. Result : Psychological factors due to grieving and previous medical history are factors that cause hyperemesis gravidarum.main nursing diagnosis is Imbalance of nutrition less than body requirements related to lack of dietary intake due to nausea and vomiting. Nursing interventions include management of nausea and vomiting, and monitoring of vital signs. Implementation of nursing actions according to priorities that have been made and equipped with interventions from subsequent diagnoses. Within 3x24 hours the problem of nutritional imbalance was resolved with the result criteria that the PUQE-24 score decreased gradually from a score of 11 (moderate) to 7 (moderate) on the second day, and a score of 5 (mild) was obtained. Conclusion: Hyperemesis Gravidarum can be reduced marked by the results of the PUQE-24 measurement which decreases gradually after nursing actions are carried out and an evaluation is carried out with SOAP documentation. Monitoring adequate nutritional intake and providing psychological support can reduce excessive nausea and vomiting in second trimester pregnant women. Keywords : Pregnancy, Hyperemesis Gravidarum, Nursing Care